Lobar pneumonia due to human metapneumovirus: a case report - Masanori Kawataki; Akihiro Ito; Takashi Koyama; Tadashi Ishida (International Journal of Infectious Diseases, 2024)
Human metapneumovirus (hMPV) is a respiratory pathogen that can cause lower respiratory tract infections and pneumonia in immunocompetent adults. Pneumonia caused by hMPV is reportedly more likely to cause bronchial wall thickening and ground-glass opacity (GGO). A 44-year-old woman with no significant medical history developed fever, cough, and nausea. Computed tomography of the chest showed scattered GGOs in the right upper lobe and infiltrating shadows with air bronchograms in the left lingual and bilateral lower lobes. The patient was admitted to our hospital for further evaluation. Atypical pneumonia was suspected and lascufloxacin (LSFX) was started. Multiplex polymerase chain reaction (PCR) detected hMPV on hospital day 2 using the FilmArray Respiratory Panel 2.1. Pneumonia due to hMPV was suspected and LSFX was discontinued. The patient subsequently showed spontaneous improvement and was discharged on hospital day 6 after admission. After discharge, pneumonia continued to improve. Early detection of respiratory pathogens using multiplex PCR can help determine the appropriate treatment strategy. As hMPV can also cause lobar pneumonia, we should consider pneumonia due to hMPV in the differential diagnosis of lobar pneumonia.